Analogues of Dehydroacetic Acid as Selective and Potent Agonists of an Ectopic Odorant Receptor through a Combination of Hydrophilic and Hydrophobic Interactions. (15th March 2017) - Park, Bernie Byunghoon; Lee, NaHye; Kim, YunHye; Jae, YoonGyu; Choi, Seunghyun; Kang, NaNa; Hong, Yu Ri; Ok, Kiwon; Cho, Jeonghee; Jeon, Young Ho; Lee, Eun Hee; Byun, Youngjoo; et al.
Abstract: Identification of potent agonists of odorant receptors (ORs), a major class of G protein‐coupled receptors, remains challenging due to complex receptor–ligand interactions. ORs are present in both olfactory and non‐chemosensory tissues, indicating roles beyond odor detection that may include modulating physiological functions in non‐olfactory tissues. Selective and potent agonists specific for particular ORs can be used to investigate physiological functions of ORs in non‐chemosensory tissues. In this study, we designed and synthesized novel synthetic dehydroacetic acid analogues as agonists of odorant receptor 895 (Olfr895) expressed in bladder. Among the synthesized analogues, ( E )‐3‐(( E )‐1‐hydroxy‐3‐(piperidin‐1‐yl)allylidene)‐6‐methyl‐2 H ‐pyran‐2, 4(3 H )‐dione (10 ) exhibited extremely high agonistic activity for Olfr895 in Dual‐Glo luciferase reporter (EC50 =9 nm ), Ca 2+ imaging, and chemotactic migration assays. Molecular docking and site‐directed mutagenesis studies suggested that a combination of hydrophilic and hydrophobic interactions is central to the selective and specific binding of10 to Olfr895. The design of agonists armed with both hydrophilic and hydrophobic portions could therefore lead to highly potent and selective ligands for ectopic ORs. Abstract : Beyond sensory : Dehydroacetic acid analogues were synthesized and evaluated as agonists of the ectopic odorant receptor 895 (Olfr895), which is expressed in the bladder. The most promising compound exhibited strong activation of Olfr895, with an EC50 value of 9 nm in luciferase reporter assays. In vitro Ca 2+ imaging, chemotactic migration, and site‐directed mutagenesis experiments indicate that this compound is a highly potent and selective agonist for Olfr895 and can be used to investigate its physiological functions.